Preclinical study of boron neutron capture therapy for bone metastasis using human breast cancer cell lines. (November 2020) - Andoh, Tooru; Fujimoto, Takuya; Satani, Ryoichi; Suzuki, Minoru; Wada, Keijiro; Sudo, Tamotsu; Sakurai, Yoshinori; Tanaka, Hiroki; Takata, Takushi; Ichikawa, Hideki
Abstract: Bone metastasis has a major impact on the quality of life that general therapy cannot control. We established a bone metastasis model with a human breast cancer cell line and investigated the therapeutic effect of boron neutron capture therapy (BNCT). BNCT suppressed tumor growth in cases of intramedullary small tumors without damaging normal tissues, providing preliminary evidence that it is a potentially new therapeutic option for controlling tumor growth from bone metastasis. Further research is warranted for its clinical application. Highlights: BNCT trial was performed on a bone metastasis model of breast cancer. A suppression of the tumor-growth was seen by single BNCT with the use of L-BPA. BNCT may be an effective therapeutic option for bone metastasis originating from breast cancer.